Accounting Information System In The Decision-Making Of Fixed Asset Investments At PT. Sawit Jujuhan Abadi (Asian Agri Group) - Edy Prabowo; Eka Siskawati; Nurul Fauzi (UNIVED Press, 2024)
This research delves into the pivotal role of Accounting Information Systems (AIS) in the decision-making process concerning fixed asset investments at PT. Sawit Jujuhan Abadi, a subsidiary of the esteemed Asian Agri Group. The study aims to scrutinize the existing practices of AIS within the company and assess the managerial readiness to adopt the E-Capex Accounting Information System model. This model is specifically designed to facilitate effective decision-making in the realm of fixed asset investments. Through an in-depth analysis, the research endeavors to provide valuable insights into the utilization of AIS, shedding light on its impact on decision-making processes related to fixed asset investments. The study anticipates contributing practical knowledge to the management of PT. Sawit Jujuhan Abadi, empowering them to make more informed and strategic decisions. Furthermore, the research seeks to enhance the broader understanding of AIS applications in the dynamic context of fixed asset investments within the Asian Agri Group.